Crimmitschauer Textilarbeiterinnen im Kampf für den Zehnstundentag. Orig. in IML, Berlin, neg. III-4-C 9.10
Crimmitschauer Textilarbeiterinnen im Kampf für den Zehnstundentag. Orig. in IML, Berlin, neg. III-4-C 9.10.